2013
DOI: 10.1074/jbc.m112.437145
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine- and Amphetamine-regulated Transcript (CART) Protects Beta Cells against Glucotoxicity and Increases Cell Proliferation

Abstract: Background: CART potentiates GSIS in pancreatic beta cells and confers neuroprotection. Results: CART reduced beta cell apoptosis, induced phosphorylation of IRS, PKB, p44/42 MAPK, and CREB, and increased proliferation. Conclusion: CART protects beta cells from glucotoxicity and activates kinases important for cell survival and proliferation. Significance: CART is a novel islet peptide that improves glycemia and beta cell viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 63 publications
0
22
0
1
Order By: Relevance
“…Interestingly, in the presence of GLP-1 or cyclic AMPproducing agents, CART 55-102 consistently amplifies insulin secretion from rodent islets in a protein kinase A (PKA)-dependent manner [7,21,24]. CART 55-102 also protects beta cells against glucotoxicity and promotes survival and induces proliferation of beta cells [17]. In addition, it inhibits glucagon secretion of human and mouse islets at low glucose [7], and modestly inhibits somatostatin secretion from rat islets [17,24].…”
Section: Cart Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in the presence of GLP-1 or cyclic AMPproducing agents, CART 55-102 consistently amplifies insulin secretion from rodent islets in a protein kinase A (PKA)-dependent manner [7,21,24]. CART 55-102 also protects beta cells against glucotoxicity and promotes survival and induces proliferation of beta cells [17]. In addition, it inhibits glucagon secretion of human and mouse islets at low glucose [7], and modestly inhibits somatostatin secretion from rat islets [17,24].…”
Section: Cart Expressionmentioning
confidence: 99%
“…CART 55-102 also protects beta cells against glucotoxicity and promotes survival and induces proliferation of beta cells [17]. In addition, it inhibits glucagon secretion of human and mouse islets at low glucose [7], and modestly inhibits somatostatin secretion from rat islets [17,24].…”
Section: Cart Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that addition of exogenous CART protects against glucotoxicity-induced beta-cell death (Sathanoori et al, 2013). To rule out that the observed effects of CART KD were secondary to reduced cell viability, we next assessed whether silencing of CART would influence beta-cell survival using the ApoTox-Glo Triplex assay.…”
Section: Cart Silencing Induces Beta-cell Apoptosis In Ins-1 (832/13)mentioning
confidence: 99%
“…Furthermore, administration of exogenous CART inhibits glucagon secretion in human and rodent islets as well as in vivo in mice due to reduced alpha-cell exocytosis (Abels et al, 2016). Furthermore, exogenous CART protects beta-cells against glucotoxicity-induced cell death in vitro in INS-1 (832/13) beta-cells Abbreviations: alpha-KIC, alpha-ketoisocaproate; CART, cocaine-and amphetamine-regulated transcript; CARTPT, human gene encoding CART; FCCP, carbonyl cyanide 4-(trifluoromethoxy)phenylhydrazone; GSIS, glucose-stimulated insulin secretion; KD, knock-down; OM, oligomycin; RRP, ready releasable pool.and rat islets (Sathanoori et al, 2013). In addition, endogenous beta-cell CART is upregulated in T2D patients as well as in several rodent models of T2D (Abels et al, 2016;, likely as a homeostatic response attempting to overcome hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%